COMPARATIVE PROFESSIONAL ACCOUNTANCY–SOUTH AMERICA. - Murphy, Mary E. (The Accounting Review, 1960)
Abstract The article discusses professional accountancy in South America. In Argentina, at the present time, the profession is regulated by an act passed in March, 1945, by which those possessing a university diploma are entered in an Accountants' Register. Non-graduates also can be entered in this register, if they submitted an application in 1945 and were active as independent accountants before December 31, 1944. An accountant can serve in a public capacity only if his name was mentioned in the register. In Brazil, to follow the accounting profession, it is necessary to obtain a diploma from a recognized college, subject to inspection by the Ministry of Education. This diploma must then be registered at the Superintendence of Commercial Teaching and at the appropriate regional council of accountancy. In Chile, accountancy is in its initial stages as a profession. British Chartered Accountants established offices in Valparaiso as early as 1912, and branches have been set up in Santiago, Concepción, and other cities.